PROVISION OF LACTATION CLINIC IN COMPANIES IN SEMARANG CITY: A REVIEW OF POLICY IMPLEMENTATION - Khalishah, Jihan Nurul Qamariah; Sriatmi, Ayun; Budiyanti, Rani Tiyas (Universitas Airlangga, 2024)
Background: As of 2022, Semarang City has 4,083 companies. However, according to the Labor Office of Semarang City, only 109 out of 529 companies provide lactation clinics. In addition, based on previous research in Pedurungan, Semarang City, most of the women (83,3%) who work do not practice exclusive breastfeeding (EBF), one reason being the lack of lactation clinics in companies. Aims: This study examines the implementation of lactation clinic policies in companies in Semarang City. Methods: This study used a qualitative method with a descriptive approach. The research variables included effectiveness, consistency, relevance, organizational structure, resources, sociocultural environment, economic environment, organizational culture, geographic environment, knowledge and skills, communication, and political support. Informants were selected based on purposive criteria, involving eight key informants and 18 supporting informants from eight companies in Semarang City. Results: Lactation clinic policies were ineffective because companies were unaware of their contents and perceived them as recommendations only. On the contrary, working mothers who breastfed recognized the benefits of the policies and considered them relevant. Three out of eight companies provided lactation clinics. The people in charge had yet to be appointed due to the different capacities of the companies. Due to a lack of support from the sociocultural environment, working mothers needed more awareness of the importance of breastfeeding. However, the companies' economic and geographic environments and organizational culture were relatively favorable. Meanwhile, adequate dissemination could have helped communication. In addition, most companies do not provide lactation clinics or recommend formula milk. Conclusion: The current policies have not adequately supported the provision of lactation clinics in companies in Semarang City. To address this issue, lactation clinics should be classified according to the companies' capacities. It is also necessary to develop a leading sector that is transparent and responsible for supervising the provision of lactation clinics. Keywords: exclusive breastfeeding in workplace, lactation clinic, policy implementation